SENSLOPE development of alternative cost-effective instrumentation and sensor networks for monitoring landslides and slope features - de Dios, Rosanno JC
A system consisting of alternative instrumentation for slope deformation and soil-water status was designed, developed, and tested on a miniature slope model. The landslide monitoring system is composed of a sensor column array that is installed vertically into the slope. The sensor column array consists of pipe segments each containing a tri-axial accelerometer for tilt measurements and capacitive type sensors for soil moisture measurements. An improvised observation well for pore water pressure (PWP) measurements is also integrated into the system. Measurements taken in each segment are accessed via Controller Area Network (CAN) communications protocol. The sensor column and PWP sensor are communicated wirelessly with a central base station via a Wi-Fi link. Data is collected, stored, processed and displayed via the Python-based GUI on the base station. The results of this study with the National Institute of Geological Sciences (NIGS) aim to give insight regarding the relationship between rainfall intensity, pore pressure development and ground movements. The small-scale testing of the landslide monitoring system seeks to evaluate the robustness of the system as well as validate the analytical model for predicting landslides prior to deployment in the field.